Os mecanismos de coesão e coerência para a configuração de reportagens escritas por alunos do 9º ano do Ensino fundamental - Silva, Maria Quitéria da (2019)
This dissertation proposes to reflect about aspects of textuality related to the configuration of reporting textual genre in a didactic work developed on the existing professions in the community in which a municipal school of Maceió-AL is inserted. The research, ethnographic, focuses on Languages and Literacies area of research line Reading and Text Production and Educational Practice of Professional Master of Letters/Profletras, Faculty of Letters of the Federal University of Alagoas (UFAL). The data obtained in the classroom, a total of 21 texts, consist of two, three or four versions, the original and rewritten submitted to interactive textual intervention (CALIL, 2000; Ruiz, 2015), in which the teacher writes notes pointing aspects for the improvement of texts. Among these productions, four texts were selected in initial version (manuscript), four in second version (manuscript), one in third version (manuscript) and four texts in final version (diagrammed), in a total of 13 versions of texts for comparative analysis. The didactic work, for the organization of a reporting board about the professions, started with the development of the proposal presented in Unit I: Work, from the chapter titled: Our Daily Work, from the Portuguese-LDP Didactic Book - Eja Moderna - 9th grade of primary school adopted by the school. For the analyzes and reflections on the aspects of textuality of the textual genre worked, we used the studies on textual cohesion and coherence (Antunes 2005, 2010, KOCH, 2016; KOCH; TRAVAGLIA, 2015), as well as studies on textual genres (MARCUSCHI, 2008, 2010), the reporting textual genre (BAHIA, 2009, BONINI 2014, FARIA, 2016, KINDERMANN, 2014), among others. The research aimed to answer the following questions: How do 9th grade students articulate the mechanisms of cohesion and coherence directed to the report genre configuration and what changes in this specific configuration after didactic intervention? Our results indicate that the latest version, the markers used contribute most significantly to the flow and direction of the text. It´s also possible to affirm that the notes, pointed out by Ruiz (2015), had an effect, contributing to the construction of a more cohesive and coherent text, reinforcing the idea of the importance of a more detailed study of the cohesion for a better development of the texts, aiming at its thematic progression.